Cytotoxicity of Doxycycline Effluent Generated by the Fenton Process. (14th October 2014) - Borghi, Alexandre Augusto; Oliveira-Nascimento, Laura; Stephano, Marco Antônio; Monteiro de Souza, Paula; Converti, Attilio; Alves Palma, Mauri Sérgio
Abstract : This study aims at determining the Minimum Inhibitory Concentration with Escherichia coli ATCC 25922 and cytotoxicity to L929 cells (ATCC CCL-1) of the waste generated by doxycycline degradation by the Fenton process. This process has shown promise in this treatment thanks mainly to the fact that the waste did not show any relevant inhibitory effect on the test organism and no cytotoxicity to L-929 cells, thus demonstrating that the antibiotic properties were inactivated.